América del Sur en el comercio global (2007-2016) - Fernández Rodríguez, Milú O. V. (Pontificia Universidad Católica del Perú. Fondo Editorial, 2018)
This paper analyzes the main characteristics of the trade of goods and services of South America according the changes in the international context. Mainly, it analyzes the commercial flows, the main commercial partners and the main characteristics of the goods and services marketed. In addition, the analysis is done at the region and country level.

El presente trabajo analiza las principales características del comercio de bienes y servicios de América del Sur ante los cambios en el contexto internacional. Principalmente, se analizan los flujos comerciales, los principales socios comerciales y las principales características de los bienes y servicios comercializados. Además, el análisis se realiza a nivel de región y país.
South America in global commerce (2007-2016)
Keywords: América del Sur; Comercio; Bienes; Servicios; https://purl.org/pe-repo/ocde/ford#5.09.01